Improved identification of secondary hypertension: use of a systematic protocol - Kotliar, Carol Virginia (2018)
Background: The accurate identification and diagnosis of secondary hypertension is critical, especially while atherosclerotic cardiovascular heart disease continues to be the leading cause of death in the industrialized world. Nevertheless, despite the existence of diagnostic tools, there are significant variations of the estimated prevalence of secondary hypertension, due to multiple etiologies and suboptimal recognition. This study demonstrates the results of using a systematic and protocolled approach to improve recognition of the presence of secondary hypertension. In the future, this questionnaire can be a quick and effective tool to unveil secondary hypertension in a broad array of clinical settings. Methods: A total of 28,633 consecutive patients from January 1, 2007 to January 1, 2017 were diagnosed as having primary or secondary hypertension, utilizing the International Code of Diseases. Patients were located at the Center of Hypertension, Institute of Cardiology at Austral University Hospital, Buenos Aires, Argentina and were then further classified as having TRH, or non-resistant hypertension, to which a systematic protocol was employed in search for secondary hypertension. The confirmation of secondary hypertension was subsequently confirmed by diagnostic laboratory and imaging techniques in a hospital setting. Results: A final population of 12,284 patients with treatment resistant hypertension (TRH) and nontreatment resistant hypertension (NTRH) were included in this study, where an etiology of secondary hypertension was identified in 50.9% and 36% of patients in each treatment group, respectively. Physicians used confirmatory laboratory testing and imaging of patients who were identified as having a cause for their secondary hypertension, with no significant differences in sex, age and body mass index (BMI) among study groups. Conclusions: These results illustrate the prevalence and distribution of the causes of secondary hypertension using a systematic, protocolled approach, which revealed a higher percentage of secondary hypertension than previously reported. This tool may be used by healthcare providers to ensure the appropriate recognition of secondary causes of hypertension in a wider range of patients with high blood pressure beyond resistant hypertension, changing the diagnostic paradigm of this condition.